Compostos bioativos de polpa e subprodutos de frutas tropicais: quantificação, atividade antimicrobiana e encapsulamento - Silva, Larissa Morais Ribeiro da (2014)
Currently, there is a demand for natural antimicrobials for use in the food industry. Some tropical fruits have a promising potential , not investigated at the moment. This study aimed to identify and quantify resveratrol, quercetin and coumarin in pulps and byproducts of tropical fruits, develop nanoparticles with extracts that showed higher levels of these compounds and evaluate the antimicrobial activity against Listeria sp. and E. coli K12. The Surinam cherry and mango byproducts, as well as caja, acerola and Surinam cherry pulps showed higher levels of quercetin, representing sources of this substance. Guava and Surinam cherry byproducts showed resveratrol in their content, may be considered as sources of this compound. Similarly, for coumarin, passion fruit, guava and Surinam cherry byproducts, as well as mango pulp, can be considered natural sources. Among the analyzed material, the acerola pulp and passion fruit and guava byproducts were selected for further characterization and nanoencapsulation. Nanoparticles synthesized using co-glycolide (PLGA) 65:35 poly lactide showed higher particle sizes (from 153.37 to 376.70 nm), as compared with the synthesized PLGA 50:50 (136.53 to 369.25 nm). All samples showed low polydispersity index, corresponding to a heterogeneous distribution in the emulsion analyzed for particle size obtained. The nanoparticles synthesized with PLGA 65:35 showed higher encapsulation efficiency, with the exception of the sample containing acerola (best EE % for PLGA 50:50) and for the release analysis, all samples showed similar behavior, providing maximum release compound within 30 minutes, with constant release thereafter during 72 hours analysis. In general, nanoparticles synthesized with PLGA 65:35 had lower minimum inhibitory concentration for E. coli K12 and L. monocytogenes compared with the 50:50 PLGA nanoparticles synthesized. The synthesis of PLGA nanoparticles using extracts of fruits (especially using PLGA 65:35) may have important applications in the food industry to inhibit microorganisms (E. coli K12 and L. monocytogenes). Besides antimicrobial activity, these compounds show various fruits with antioxidant properties, which are responsible for reducing the risk of various diseases.